Sub-macroscopic skin presentation of acromegaly and effect of pituitary tumor surgery: A study using dermatoscopy and ultra-high-frequency ultrasound - Guo, Xiaopeng; Wang, Yukun; Yao, Yong; Bao, Xinjie; Duan, Lian; Zhu, Huijuan; Xing, Bing; Liu, Jie (Frontiers in Endocrinology, 2023)
Objective: Excessive growth hormone and insulin-like growth factor 1 contribute to cutaneous changes in acromegaly. We investigated the sub-macroscopic skin manifestation of acromegaly patients and explored its reversibility upon hormone reduction after pituitary adenoma surgery. Design: Prospectively cohort study. Methods: We enrolled 26 patients with acromegaly and 26 patients with non-functioning pituitary adenomas undergoing pituitary adenomectomy at Peking Union Medical College Hospital from July 2021 to March 2022. Skin presentations were evaluated by dermatoscopy and ultra-high-frequency ultrasound before and after surgery. Results: Skin thickening, follicular plugs, perifollicular pigmentations, perifollicular orange haloes, red structureless areas, increased hair shafts, honeycomb-like pigmentations, widened dermatoglyphics, dilated appendage openings, excessive seborrhea, hyperhidrosis, enlarged pores, and acne-like lesions were commonly occuring in acromegaly patients, and their incidences were higher than the controls (P<0.05). At 3-month follow-up after surgery, the thickness of skin reduced (4.0±0.4 to 3.7±0.4, P=0.007), the incidences of hyperhidrosis (92.3% to 69.2%, P=0.035) and acne-like lesions (53.8% to 26.9%, P=0.048) declined, and the severity of multiple cutaneous lesions improved. Patients with surgical endocrine remission (53.8%) had greater declines in the thickness of skin than those without remission. Patients with improvement of >1 skin lesions were younger (P=0.028) and had higher baseline GH levels (P=0.021) than those with improvement of ≤1 skin lesion. Conclusions: Dermatoscopy and ultra-high-frequency ultrasound provided augmented visual examination of the cutaneous changes in acromegaly. Some of the skin lesions could improve or reverse after pituitary surgery. Baseline GH levels, age, and endocrine remission were correlated with skin improvement at 3-month follow-up.